Systematic Review and Meta-Analysis: Effect of Zinc Levels in COVID-19 Patients on Their Clinical Severity - Annisa, Ika Nur; Yuniasih, Dewi; Sukirto, Novi Wijayanti (Ahmad Dahlan Medical Journal, 2023)
Background: COVID-19 is a new type of Coronavirus that can cause ARDS and make it a worldwide pandemic. Treatment for COVID-19 is based on the clinical severity of COVID-19. Zinc has anti-inflammatory, antiviral, and antioxidant effects given as an adjuvant therapy for the treatment of COVID-19. Prolonged zinc deficiency is a risk factor for severe COVID-19. Methods: This systematic review and meta-analysis study used 4 databases namely ScienceDirect, Cochrane Library, ProQuest, and PubMed. The keywords used are “Zinc” OR “Severity COVID-19” AND “Zinc Deficiency” OR “Mortality COVID-19” AND “Zinc” OR “Clinical Severity COVID-19” AND “Zinc Deficiency” OR “Clinical Severity COVID- 19”. The articles identified are articles that are relevant to the title of research, published internationally, accessed free of charge, published between 2019-2021, published in accredited journals Results: Out of 8,330 article titles, 944 were excluded due to double counting in each database. A total of 7,371 articles were excluded because they did not match the title of the study, did not match the research method, used another language, did not match the year of publication. A total of 15 articles were included in the qualitative synthesis. Five studies were included in the meta-analysis. Three studies were analyzed with the results that the average zinc level of COVID-19 patients was not much different from that of healthy patients with a mean difference of 1.73 (95% CI -39.14-42.60). Two studies were analyzed with low zinc levels in patients with severe COVID-19 associated with the need to enter the intensive care unit with an OR of 3.62 The SARS-CoV-2 virus spreads through droplets that are expelled while coughing or sneezing. Conclusion: The average zinc level of COVID-19 patients is not different from that of healthy patients, but low zinc levels in patients with severe COVID-19 are associated with the need to enter the intensive care unit.